HUBUNGAN ANTARA PENGETAHUAN DAN SIKAP TENAGA KESEHATAN TERHADAP PENGELOLAAN LIMBAH MEDIS DI PUSKESMAS SELAYO, SUMATERA BARAT - Kartika Wulandari; Yusriani Sapta Dewi (FT-USNI, 2022)
In this day and age that waste is a problem serious enough, so many efforts to reduce poverty by means of reducing, recycling and destroy it. The producing a great variety of waste in the form of of liquids, solid and gas. Is not a good medical management waste could cause problem with health care and the environment. The purpose of this study was to determine the relationship of knowledgeand attitudes of health workers with medical waste management at community health centerSelayo. The research is of research the quantitative cross sectional. The population in this research is all health workers of community health center Selayo totaled 60 people. The sample technique used is the total sampling. The sample in this research is all health workers medical waste of 60 people.The analysis used in this research use software IBM SPSS Statistics Version 26. The result showed a value of knowledge of health workers (X1) -value =0,000 < significance (Y)= 0,05 which means there is a relationship between knowledge of health workers with medical waste management at community health center Selayo an d a value of attitudes of health workers (X2) -value =0,003 <significance (Y)= 0,05 which means there is a relationship between attitude of health workers with medical waste management at community health center Selayo. A value of ( X1) and value (X2) value=0,000< significance (Y)=0,05 which means there is a relationship between knowledge and attitudes of health workers with medical waste management at community health center Selayo.The existence of a relationship between knowledge and attitudes of health workers with medical waste management, then to expect every health workershould have a good knowledge of and attitudes towards the medical waste management in community health center so that actions taken in the handle and manage medical waste can be run correctly